Role of biochar in anaerobic microbiome enrichment and methane production enhancement during olive mill wastewater biomethanization - Nozha Abid; Fatma Karray; Imen Kallel; Mariam Slim; Abdellatif Barakat; Abdellatif Barakat; Najla Mhiri; Mohamed Chamkha; Sami Sayadi (Frontiers in Bioengineering and Biotechnology, 2023)
The current research work attempted to investigate, for the first time, the impact of biochar addition, on anaerobic digestion of olive mill wastewater with different initial chemical oxygen demand loads in batch cultures (10 g/L, 15 g/L, and 20 g/L). Methane yields were compared by applying one-way analysis of variance (ANOVA) followed by post-hoc Tukey’s analysis. The results demonstrated that adding at 5 g/L biochar to olive mill wastewater with an initial chemical oxygen demand load of 20 g/L increased methane yield by 97.8% and mitigated volatile fatty acid accumulation compared to the control batch. According to the results of microbial community succession revealed by the Illumina amplicon sequencing, biochar supplementation significantly increased diversity of the microbial community and improved the abundance of potential genera involved in direct interspecies electron transfer, including Methanothrix and Methanosarcina. Consequently, biochar can be a promising alternative in terms of the recovery of metabolic activity during anaerobic digestion of olive mill wastewater at a large scale.